Digital Leadership Impact on Organizational Culture and Learning Innovation in Islamic Education - Muh ibnu sholeh; Mohamed Ramadan Abd Allah Mohamed; Nur ‘Azah; M. Munif; Muhammad Haris (International Journal of Multidisciplinary Research and Innovation, 2025)
This study aims to analyze the impact of digital leadership on organizational culture and learning innovation at MA Unggulan Darul Ulum STEP-2. The research employs a mixed-methods approach, combining quantitative and qualitative methodologies. Quantitative data were collected through questionnaires involving 133 respondents, while qualitative data were obtained through interviews with the school principal, teachers, and students. Data analysis techniques include reliability testing, Pearson correlation, and simple linear regression to measure the relationship between digital leadership, organizational culture, and learning innovation. The quantitative analysis results indicate that digital leadership has a very weak correlation with organizational culture (r = -0.0205) and a low influence on learning innovation based on linear regression results (R² = 0.167). Interviews with the school principal and teachers revealed that the main challenges in implementing digital leadership include infrastructure limitations, teacher readiness, and resistance to change. The findings suggest that digital leadership needs to be supported by more structured strategies, such as teacher training, digital infrastructure enhancement, and strengthening a technology-based organizational culture. With the right approach, digital leadership can become a key factor in enhancing learning innovation in Islamic education. Digital leadership has been implemented at MA Unggulan Darul Ulum STEP-2, but it has not yet had a significant impact on organizational culture and learning innovation. Therefore, a more comprehensive approach is needed to improve the effectiveness of digital leadership in education.